Pengaruh Kebijakan Biaya dan Kualitas Layanan Terhadap Kepuasan Pelanggan Pada Ganesha Operation Muara Bulian - Siti Marlina; Benni Saputra (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study is to explain the influence of cost and service quality policies on customersatisfaction at Ganesha Operation Muara Bulian. The research approach is used through qualitativemethods of collecting data on observation and interviews. The analytical method used is a qualitativeapproach with data reduction, data presentation and conclusion drawing. The samples in this study were55 people. Data were analyzed using multiple linear regression, t test, f test and coef icient ofdetermination simultaneously and using the SPSS program to determine the factors that influencecustomer satisfaction. The conclusions in this study are: The value of multiple linear regression equations, namely Y = 2.072 + 0.982X1 + 0.951X2. It was concluded that if the cost policy (X1) and service quality(X2) = 0, then customer satisfaction (Y) was 2.072, if the cost policy (X1) increased by one unit, customersatisfaction rose by 0.982 assuming service quality (X2) = 0 or constant. And if service quality (X2)increases by one unit, customer satisfaction increases by 0.951 assuming a cost policy variable (X1) = 0or constant. T test with the most dominant value is the cost policy variable of 6,858 thitung> 1,675 ttable. While the F Test with a value of Fcount = 147.067> Ftable = 3.18 means that the variable policy costsand service quality af ect customer satisfaction. For the determination coef icient test of 84.4% which isinfluenced by cost and service quality policies on customer satisfaction and the remaining 15.6% isinfluenced by other factors not examined.